Ankle taping techniques on the ATP tennis circuit - Bastholt, P. (2001)
This article describes procedures used for ankle taping on the ATP tennis circuit. Ankle taping often allows sports activity to continue in the competitive athlete while injury healing progresses by a combination of mechanical, antalgic, exteroceptive, proprioceptive and psychological effects. The materials required to tape one ankle are mentioned, recommendations for proper taping are given. Especially the rigid ankle tape (American) and the the mixed tape are explained.